Pengembangan Lembar Kegiatan Siswa (LKS) Problem Based Learning (PBL) Pada Materi Sistem Persamaan Linier Dua Variabel di Kelas VIII SMP - Audina, Nia; Yuliani, Refi Elfira; Muslimin, Muslimin (JURNAL PENELITIAN PENDIDIKAN MATEMATIKA, 2021)
The objective of this study is to create educational materials based learning valid and practical for both SPLDV material study in junior high and to identify the potential effect of LKS that has developed. The methods of research used development research. The development of this LKS was based on two phases of expert review, one-to-one, small group, and field test. Based on the results of this research obtained a valid and practical LKS. These are valid according to the expert assessment (validator) that the well developed LKS, based on material (content aspects, feature worthiness and PBL assessments), language (aspect of language worthiness) and media/appearance LKS (aspect of literacy include LKS size, cover design, and LKS content design). It was pratical seen from a small group tryouts where students can use LKS easily and can be seen from the student response rate. Potential effects judging by the student study results. The results of analysis of the data done came to an average of 80.14 which meant that student study was “very good” category, which showed that their use of LKS mathematical PBL student  developed had a potential effect.